Fatigue and static characterization on the behavior of electrospun nano-fiber veil toughened composites. (4th May 2022) - Shi, Mingjun; Nakai, Asami
Abstract : This study focuses on the fatigue and static response of noncrimp fabric laminates modified with electrospun nanofiber veils; thus, the cross-ply was engaged in performing the test program. The results of static flexural tests and short-beam shear tests initially exhibited significant improvement in the flexural and interlaminar shear strength of the nanofiber modified (NM) samples due to different mechanisms. Further, the fatigue tests were conducted under the load-control fatigue condition, and the NM configuration exhibited high deflection and low stiffness decrease rate during the progressive damage. Notably, the fatigue strength of the NM configuration was 1.7 times higher than the virgin configuration, and the run-out point analysis revealed that the nanofiber veil has excellent potential to extend the material fatigue strength range and optimize the fatigue energy absorption capability of composite material. Finally, although the residual strength of the pre-cycling specimens reduced with an increase in load level, the stiffness reduction could not accurately predict the residual strength of the sample.